2009
DOI: 10.1523/jneurosci.2114-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spared and Impaired Olfactory Abilities after Thalamic Lesions

Abstract: Olfactory information reaches olfactory cortex without a thalamic relay. This neuroanatomical substrate has combined with functional findings to suggest that, in olfaction, the typical thalamic role in sensory processing has shifted to the olfactory bulb or olfactory cortex. With this in mind, we set out to ask whether the thalamus at all plays a significant functional role in human olfaction. We tested olfactory function in 17 patients with unilateral focal thalamic lesions and in age-matched healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…Although olfactory processing has a nonobligatory thalamic relay (e.g., in contrast to vision), thalamic lesions cause impairments in odor functioning (29), i.e., in identification and in evaluation of pleasantness. Moreover, it has been suggested that thalamic nuclei receive indirect olfactory input from olfactory cortex (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although olfactory processing has a nonobligatory thalamic relay (e.g., in contrast to vision), thalamic lesions cause impairments in odor functioning (29), i.e., in identification and in evaluation of pleasantness. Moreover, it has been suggested that thalamic nuclei receive indirect olfactory input from olfactory cortex (30).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of MDT lesions on olfactory learning is further supported by the study of Kawagoe et al (2007) who showed that MDT units in behaving rats may support associative learning by encoding the reward value of the olfactory cue. Finally, as in smaller animals, humans with thalamic damage present deficits in both odor discrimination and odor identification but not in odor detection (Potter and Butters, 1980; Sela et al, 2009; Tham et al, 2011b). Interestingly, attention deficits may also underlie the problems of MDT-lesioned rodents and humans in performing difficult discrimination tasks given the role of MDT in modulating attention in olfaction (Olofsson et al, 2013; Spence et al, 2001; Tham et al, 2009, 2011a,b; Zelano et al, 2011).…”
Section: The Role Of the Olfactory Cortex In Odor Perceptionmentioning
confidence: 91%
“…Linked to this distortion of odor preference, studies of patients with damage in the MDT following cerebral hemorrhage, ischemic infarctions, or abscess provide similar evidence. In fact, olfactory hedonic judgments were found to be altered in single-case patient studies (Asai et al, 2008; Rousseaux et al, 1996) as well as in a larger set of patients with thalamic lesions (Sela et al, 2009). Relative to discrimination and learning, Eichenbaum et al (1980) were the first to report that rats with MDT lesions do not have olfactory detection deficits but require more trials to reach the performance criterion in a difficult discrimination task (stimuli similarity, novelty, or reversal; Eichenbaum et al, 1980; Staubli et al, 1987).…”
Section: The Role Of the Olfactory Cortex In Odor Perceptionmentioning
confidence: 98%
“…Human neuroimaging (De Araujo et al, 2003;Small et al, 2004) and single-unit recordings in nonhuman primates (Rolls and Baylis, 1994) have shown gustatory and olfactory interactions in OFC. The mediodorsal thalamus receives olfactory information from PIR (Plailly et al, 2008), is reciprocally connected to GC, basolateral amygdale, and OFC (Krettek and Price, 1977;Ray and Price, 1992), and humans with mediodorsal thalamus lesions report lower hedonic ratings for experienced odorants and flavors (Rousseaux et al, 1996;Asai et al, 2008;Sela et al, 2009;Tham et al, 2011). The interaction between these higher-order areas and primary sensory cortices could modulate the response to odorants in GC, particularly in the case of palatability coding, bimodal neurons identified in this study.…”
Section: Chemosensory Multimodality In Gcmentioning
confidence: 99%